Immunotherapy With Subcutaneous Immunoglobulin or Plasmapheresis in Patients With Postural Orthostatic Tachycardia Syndrome (POTS). (5th December 2022) - Nelson, Renee; Kesterson, Katrina; Schofield, Jill; Blitshteyn, Svetlana
Abstract : Objective: To assess improvement in autonomic symptoms and functional impairment following immunotherapy with subcutaneous immunoglobulin (SCIG) or plasmapheresis (PLEX) in patients with postural orthostatic tachycardia syndrome (POTS). Background: POTS is a common autonomic disorder defined by an increased heart rate of at least 30 bpm within 10 minutes of standing or a tilt table test, accompanied by orthostatic intolerance, fatigue, dizziness, and headache. Despite pharmacologic and non-pharmacologic therapy, the marked functional impairment associated with POTS reflects great need for improved treatment. Autoimmunity has emerged as a leading etiology of POTS, with case series describing successful treatment with IVIG. To our knowledge, treatment with SCIG has not been described previously. Design/Methods: Clinical history of seven patients with POTS treated with SCIG or PLEX was reviewed. Response to treatment was assessed using COMPASS-31 and functional ability scale (FAS) completed retrospectively pre- and 3-12 months post-treatment with SCIG or PLEX. Patients with comorbid defined autoimmune disorders or immune deficiency requiring treatment with immunotherapy were excluded from the study. Results: Of seven patients, all female, ages 28-57, five received SCIG and two received PLEX. Four had comorbid small fiber neuropathy and five had various positive antibodies at low titers. Across all patients, COMPASS-31 and FAS scores improved an average of 50% and 217%, respectively. Six patients were able to discontinue or reduce oral medications and five reported being able to return to work or school. No serious adverse events were reported. Conclusions: Patients with POTS experienced significant functional improvement with reduction in autonomic symptoms following immunotherapy with SCIG or PLEX. This case series suggests that SCIG and PLEX may be safe and effective treatments for patients with severe POTS refractory to standard therapies. Randomized controlled trials are needed to determine the efficacy and safety of these long-term therapies.